웹사이트에 제공된 만성폐쇄성폐질환 건강정보와 연구문헌에 나타난 환자의 건강정보 요구의 지식구조: 텍스트 네트워크 분석 활용 - 최자윤; 임수연; 윤소영; Choi, Ja Yun; Lim, Su Yeon; Yun, So Young (Journal of Korean Academy of Nursing, 2021)
Purpose: The purpose of this study was to identify the knowledge structure of health information (HI) for chronic obstructive pulmonary disease (COPD). Methods: Keywords or meaningful morphemes from HI presented on five health-related websites (HRWs) of one national HI institute and four hospitals, as well as HI needs among patients presented in nine literature, were reviewed, refined, and analyzed using text network analysis and their co-occurrence matrix was generated. Two networks of 61 and 35 keywords, respectively, were analyzed for degree, closeness, and betweenness centrality, as well as betweenness community analysis. Results: The most common keywords pertaining to HI on HRWs were lung, inhaler, smoking, dyspnea, and infection, focusing COPD treatment. In contrast, HI needs among patients were lung, medication, support, symptom, and smoking cessation, expanding to disease management. Two common sub-topic groups in HI on HRWs were COPD overview and medication administration, whereas three common sub-topic groups in HI needs among patients in the literature were COPD overview, self-management, and emotional management. Conclusion: The knowledge structure of HI on HRWs is medically oriented, while patients need supportive information. Thus, the support system for self-management and emotional management on HRWs must be informed according to the structure of patients' needs for HI. Healthcare providers should consider presenting COPD patient-centered information on HRWs.